Pengembangan Perangkat Pembelajaran Berbasis Discoveri Learning Dengan Bantuan Cd Interaktif Untuk Meningkatkan Higher Order Thinking Skill (HOTS) Siswa (Studi Pada Siswa Kelas VIII Mata Pelajaran PAK, SMP Negeri 3 Saparua) - Wilhelmus Labobar; Claudia. M. Pattiruhu; Chyntya. L. Sapulette (Journal on Education, 2023)
This research aims to improve students' High Order Thinking Skills (HOTS) through the development of Discoveri Learning-Based Learning Tools with the Help of Interactive CDs (Studies in Class VIII PAK Subjects, SMP Negeri 3 Saparua). This type of research is development research, with a population of SMA Negeri 3 Saparua, as many as 327 students with a sample in class VIII of 31 students. The research results also found that the instrument validity test had met the validity criteria, including: Teaching materials, student responses, teacher responses, teacher ability to manage learning, student activities, learning implementation plans (RPP) and HOTS and Interactive CD ability tests above average. -average score 4.00, apart from the practicality test, teacher response questionnaire and student response questionnaire above 80%. From this research it was also found that the effectiveness of components in the form of teachers' ability to manage learning was 74% in the very good category, the average percentage of student activity was 71.39% in the good category, and the average percentage of the HOTS ability test was 90.86% and are in the high category and have achieved classical completeness, namely 93.3% of students have completed classically.